Cultural-Historical Approach to Preschoolers’ Dance Creativity: Problems and Solutions - Gorshkova, E.V. (Kulʹturno-istoricheskai͡a︡ psikhologii͡a, 2023)
The problems of the theory of dance creativity of preschoolers are analyzed from the standpoint of a cultural and historical approach. As methodological support for the analysis, we used the views of L.S. Vygotsky and his followers on children's artistic creativity, on the nature of dance and dance expressiveness, on the peculiarities of music in dance. Based on this, we analyzed three theoretical approaches to the development of dance creativity of preschoolers, and described their differences and partial mutual influences. The system of provisions of cultural and historical psychology as a methodological basis indicates ways to solve the problems of the theory of dance creativity of preschoolers, which should be figurative and meaningful, thanks to the development of the expressive language of dance, reflecting the features of the musical image and real events, relationships, experiences through the embodiment of different characters. Проблемы теории танцевального творчества дошкольников анализируются с позиций культурно-исторического подхода. В качестве методологических опор для анализа рассматриваются взгляды Л.С. Выготского, его последователей на детское художественное творчество, природу танца и танцевальной выразительности, особенности музыки в танце. Исходя из этого, рассматриваются три отечественных теоретических подхода к развитию танцевального творчества дошкольников, показаны их различия и частичные взаимовлияния. Система положений культурно-исторической психологии как методологическая основа указывает пути решения проблем теории танцевального творчества дошкольников, которое должно носить образный и осмысленный характер, благодаря освоению выразительного языка танца, с отражением особенностей не только музыкального образа, но и реальных событий, взаимоотношений, переживаний - через воплощение образов разнохарактерных персонажей.